Human resource practices and organizational support as the determinants in enhancing Vietnamese retail employee engagement: the mediating role of job enrichment - Nguyen, Khanh-Linh; Moslehpour, Massoud; Aminah, Hania; Sulistiawan, Jovi (Business: Theory and Practice, 2024)
Although employee engagement has become a vital issue in business, research on how different bundles of Human Resource (HR) practices affect employee engagement remains insufficient. This study addresses two primary aims: firstly, to investigate the direct and indirect effects of general HR practices and organizational support on employee engagement in the Vietnamese retail sector; secondly, to assess the mediating role of job enrichment in these relationships. Using Partial Least Square-Structural Equation Modeling (PLS-SEM) analysis on a sample of 796 retail employees in Vietnam, this study contributed to such a gap by investigating the mechanisms connecting different HR practices with job enrichment and engagement. Firstly, our findings confirm the direct positive impacts of organizational support and job enrichment on engagement and of organizational support and general HR practices on job enrichment itself. Secondly, although general HR practices are not found to influence employee engagement directly, their indirect influence is still significant via the full mediation of job enrichment. This research makes a substantial contribution to the current body of knowledge by enhancing our comprehension of the mechanisms that link HR practices and employee engagement. The study provides practical insights for Vietnamese retail organizations, emphasizing the importance of job enrichment, well-designed HR practices, and strong organizational support in promoting long-term employee engagement. This ultimately leads to the development of a more dedicated and committed workforce in Vietnam’s dynamic retail industry.